Special Issue Theme: Investment, Financial Risks and Corporate Sustainable Development in Asia - Othman Yong, (Asian Academy of Management Journal of Accounting and Finance, 2021)
This is a special issue of the Asian Academy of Management Journal of Accounting and Finance (AAMJAF) 2021, Volume 17, Issue 2, sponsored by Yayasan Tun Ismail Mohamed Ali YTI-UKM. The theme of this special issue is “Investment, Financial Risks and Corporate Sustainable Development in Asia”. This special issue consists of 10 papers. Each paper presents an empirical study of a specific issue related to investment, financial risks or corporate sustainable development in Asia.